Secondary formation of nitrated phenols: insights from observations during the Uintah BasinWinter Ozone Study (UBWOS) 2014 - Yuan, Bin; Liggio, John; Wentzell, Jeremy; Li, Shao-Meng; Stark, Harald; James M. Roberts; Gilman, Jessica; Lerner, Brian; Warneke, Carsten; Li, Rui; Leithead, Amy; Osthoff, Hans D.; et al. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2016)
We describe the results from online measurements of nitrated phenols using a time-of-flight chemical ionization mass spectrometer (ToF-CIMS) with acetate as reagent ion in an oil and gas production region in January and February of 2014. Strong diurnal profiles were observed for nitrated phenols, with concentration maxima at night. Based on known markers (CH4, NOx, CO2), primary emissions of nitrated phenols were not important in this study. A box model was used to simulate secondary formation of phenol, nitrophenol (NP), and dinitrophenols (DNP). The box model results indicate that oxidation of aromatics in the gas phase can explain the observed concentrations of NP and DNP in this study. Photolysis was the most efficient loss pathway for NP in the gas phase. We show that aqueous-phase reactions and heterogeneous reactions were minor sources of nitrated phenols in our study. This study demonstrates that the emergence of new ToF-CIMS (including PTR-TOF) techniques allows for the measurement of intermediate oxygenates at low levels and these measurements improve our understanding on the evolution of primary VOCs in the atmosphere.